Hubungan tingkat kecemasan terhadap kepatuhan kunjungan antenatal care (ANC) saat pandemi COVID-19 - alfiany, hanni -; Wada, fauziah H; -, sunirah - (Indonesian Academia Health Sciences Journal, 2023)
Objective: to identify  determine the relationship between anxiety levels and adherence to antenatal care visits during the COVID-19 pandemic.  Methods: This type of research uses an analytic observational method with a cross sectional approach. The sampling technique used purposive sampling with 102 respondents. Data analysis using chi-square.Results:  The results showed that the majority of respondents were at a moderate level of anxiety (48%), most of the respondents were obedient to antenatal care (62.7%), and there was a relationship between the level of anxiety and adherence to antenatal care visits during the COVID-19 pandemic in the Work Area of the District Health Center Officer. Bekasi-North with a p value of 0.042 <0.05Conclusion:  This shows that the anxiety due to the COVID-19 pandemic that is felt by pregnant women in the third trimester can affect the compliance of antenatal visits in the Work Area of the Officers Health Center.